NEEDLE STICK INJURY AND AWARENESS OF ITS MANAGEMENT AMONGST DENTAL INTERNS IN LAHORE - Mazhar, Bushra; Younus, Shoaib; Akhtar, Uzair Bin; Altaf, Ali; Munawar, Mehwish; Sajid, Malik Ali Hassan (Pakistan Armed Forces Medical Journal, 2020)
Objective: To find out the frequency and perceived causes of needle stick injuries encountered by dental interns in teaching hospitals of Lahore and to study the level of awareness and associated factors regarding needle stick injury reporting, management and hepatitis B immunization status.Study Design: Cross-sectional survey.Duration and Place of Study: Multi center, from May to Jun 2019.Methodology: Self-administered questionnaires were circulated amongst dental interns of randomly selected teaching hospitals of Lahore. Inclusion criteria was consenting dental interns completing 1-year internship by May 31st 2019.Results: Forty one interns (41%) received a 3-dose hepatitis B vaccination once, while thirty (30%) had an additional 5-yearly booster administered. Sixty three interns (63%) endorsed post exposure prophylaxis administration for hepatitis B, C and human immunodeficiency virus. Thirty three interns (33%) encountered sharp injury. No correlation was found between having knowledge about Universal Precaution Guidelines and frequency of sharp injury (p=0.218). Eleven interns (33%) reported injury to a senior. The most common cause of injury was “being rushed” 40 (40%). Eight interns (36%) identified anesthesia needle as the agent of injury. A statistically significant difference was found (p